Long-term cardiovascular outcomes after percutaneous coronary intervention in patients with systemic sclerosis - Kazutoshi Hirose; Hiroyuki Kiriyama; Shun Minatsuki; Yugo Nagae; Tatsuki Furusawa; Takashi Hiruma; Atsushi Kobayashi; Masataka Sato; Shinnosuke Sawano; Tatsuya Kamon; Hiroki Shinohara; Mizuki Miura; et al. (International Journal of Cardiology: Heart & Vasculature)
Background: Recent data have shown that systemic sclerosis (SSc) is a significant risk factor for coronary artery disease (CAD) and poorer cardiovascular outcomes in the setting of acute coronary syndrome. However, the morphological characteristics of CAD and the long-term cardiovascular outcomes in patients with concurrent SSc and CAD remain unclear. Methods: We retrospectively investigated 3,300 patients with CAD who underwent percutaneous coronary intervention (PCI) without prior myocardial infarction or coronary artery revascularization. Laboratory, echocardiographic and angiographic characteristics, and clinical outcomes were compared between patients with and without SSc according to a 1:3 propensity score-matching analysis adjusted for patient demographics and comorbidities. The primary outcome was a composite of cardiac death, myocardial infarction, and stroke, and the secondary outcome was a composite of the primary outcome and heart failure hospitalization. Results: Among all 3,300 patients, 17 (0.5 %) had SSc. The patients were classified into an SSc group (n = 17) and non-SSc group (n = 51) by propensity score matching. There were no significant differences in laboratory or echocardiographic parameters between the two groups. However, CAD tended to be more complex in the SSc group because of the higher proportion of left main trunk lesions (p = 0.100) and higher SYNergy between PCI with TAXUS™ and Cardiac Surgery (SYNTAX) score (p = 0.030). During a median follow-up of 3.1 years, patients with SSc more frequently experienced primary and secondary outcomes than those without SSc (both log-rank p < 0.02). Conclusions: Among patients with CAD, long-term cardiovascular outcomes after PCI were poorer in those with than without SSc.